Estado del arte sobre tutorías. (2012)
This article is an improvement of the research project being conducted by the Educational Research Group of the Universidad Sergio Arboleda (INVEDUSA) on academic tutorship. In this article are presented a state of the art; some practices and programs that advanced; both nationally and internationally